Generation of highly effective and stable murine alloreactive Treg cells by combined anti‐CD4 mAb, TGF‐β, and RA treatment. (9th September 2013) - Schliesser, Ulrike; Chopra, Martin; Beilhack, Andreas; Appelt, Christine; Vogel, Simone; Schumann, Julia; Panov, Ivo; Vogt, Katrin; Schlickeiser, Stephan; Olek, Sven; Wood, Kathryn; Brandt, Christine; et al.
<x xml:space="preserve">Abstract</x> The transfer of alloreactive regulatory T (aTreg) cells into transplant recipients represents an attractive treatment option to improve long‐term graft acceptance. We recently described a protocol for the generation of aTreg cells in mice using a nondepleting anti‐CD4 antibody (aCD4). Here, we investigated whether adding TGF‐β and retinoic acid (RA) or rapamycin (Rapa) can further improve aTreg‐cell generation and function. Murine CD4+ T cells were cultured with allogeneic B cells in the presence of aCD4 alone, aCD4+TGF‐β+RA or aCD4+Rapa. Addition of TGF‐β+RA or Rapa resulted in an increase of CD25+Foxp3+‐expressing T cells. Expression of CD40L and production of IFN‐γ and IL‐17 was abolished in aCD4+TGF‐β+RA aTreg cells. Additionally, aCD4+TGF‐β+RA aTreg cells showed the highest level of Helios and Neuropilin‐1 co‐expression. Although CD25+Foxp3+ cells from all culture conditions displayed complete demethylation of the Treg‐specific demethylated region, aCD4+TGF‐β+RA Treg cells showed the most stable Foxp3 expression upon restimulation. Consequently, aCD4+TGF‐β+RA aTreg cells suppressed effector T‐cell differentiation more effectively in comparison to aTreg cells harvested from all other cultures, and furthermore inhibited acute graft versus host disease and especially skin transplant rejection. Thus, addition of TGF‐β+RA seems to be superior over Rapa in stabilising the phenotype and functional capacity of aTreg cells.